Analysis of direct costs of decompressive craniectomy in victims of traumatic brain injury - Badke, Guilherme Lellis; Araujo, João Luiz Vitorino; Miura, Flávio Key; Guirado, Vinicius Monteiro de Paula; Saade, Nelson; Paiva, Aline Lariessy Campos; Avelar, Tiago Marques; Pedrozo, Charles Alfred Grander; Veiga, José Carlos Esteves (Arquivos de Neuro-Psiquiatria, 2018)
Background: Decompressive craniectomy is a procedure required in some cases of traumatic brain injury (TBI). This manuscript evaluates the direct costs and outcomes of decompressive craniectomy for TBI in a developing country and describes the epidemiological profile.Methods: A retrospective study was performed using a five-year neurosurgical database, taking a sample of patients with TBI who underwent decompressive craniectomy. Several variables were considered and a formula was developed for calculating the total cost.Results: Most patients had multiple brain lesions and the majority (69.0%) developed an infectious complication. The general mortality index was 68.8%. The total cost was R$ 2,116,960.22 (US$ 661,550.06) and the mean patient cost was R$ 66,155.00 (US$ 20,673.44).Conclusions: Decompressive craniectomy for TBI is an expensive procedure that is also associated with high morbidity and mortality. This was the first study performed in a developing country that aimed to evaluate the direct costs. Prevention measures should be a priority.
Keywords: decompressive craniectomy; brain injuries; cost and cost analysis; intracranial pressure